Metoda projektów jako strategia wcielania w praktykę idei wyłaniającego się programu - Aleksandra Maj (Problemy Wczesnej Edukacji)
The paper presents the idea of a project method which is interpreted from the perspective of two approaches to the curriculum. The first one defines the curriculum as a product – a plan with general and specific educational objectives which are set up in advance. From this point of view the curriculum is a set of documents for implementation. Another way of looking at the curriculum is via process. In this sense, the curriculum is not a physical thing, but is interpreted as what actually happens in an educational environment. In an emergent curriculum, instead of general and specific objectives, teachers formulate hypotheses derived from children’s personal experiences. Along with these hypotheses teachers formulate objectives which are flexible and correspond to the needs and interests of their students. The process of emergent curriculum development is described on the basis of the Italian strategy progettazione and the project approach by L. Katz.